Combining virtual reality and a myoelectric limb orthosis to restore active movement after stroke: a pilot study - Bermúdez i Badia, Sergi (2019)
We introduce a novel rehabilitation technology for upper limb rehabilitation after stroke that combines a virtual reality (VR) training paradigm with a myoelectric robotic limb orthosis. Our rehabilitation system is based on clinical guidelines and is designed to recruit specific motor networks to promote neuronal reorganization. The main hypothesis is that the restoration of active movement facilitates the full engagement of motor control networks during motor training. By using a robotic limb orthosis, we are able to restore active arm movement in severely affected stroke patients. In a pilot evaluation, we have successfully deployed and assessed our system with three chronic stroke patients by means of behavioral data and self-report questionnaires. The results show that our system is able to restore up to 60% of the active movement capability of patients. Further, we show that we can assess the specific contribution of the biceps/triceps movement of the paretic arm in a VR bilateral training task. Questionnaire data show enjoyment and acceptance of the developed rehabilitation system and its VR training task.